MENTAL RÖTARDE OTİSTİKLERDE YÜRÜME GELİŞİMİNDE GECİKMENİN KLİNİK PROGNOZLA İLİŞKİSİ - KORKMAZ, Barış (Cerrahpaşa Medical Journal, 2014)
Background.- This retrospective clinical study was aimed to make a statistical comparison between the mentally retarded autistic patients with delay at onset of walking and cases with no history of neuromotor delay in relation to certain clinical and laboratory features as regards to the prognosis in relation to the clinical subtypes. Design.- The study included 90 patients, 70 boys (78%) and 20 girls (22%) diagnosed as having typical symptoms of autism according to DSM-IV. The nondelay group (group A) had 64 (71 %) patients while the delay group (group B) included 26 patients (29 %). The variables considered were, demographic data (age, sex), medical history (pre-perinatal problems, presence of epileptic seizures and/or febrile convulsions), family history (consanguinity, family history of any neurodevelopmental problem such as a language disorder), medical examination (neurological examination, dysmorphism, hand dominance), behavioral features accompanying autism (such as abnormal reactivity to sensory stimuli, presence of unusual emotional !ability with sudden bursts of laugh or cry, language profile, hyperactivity), neuroimaging findings and EEG features. Results.- Significant results included the predominance of hyperactivity (p<0.001) and echolalia +cliche phrases (p<0.02) in group A, consanguinity (p<0.05), epileptic seizures (p<0.001), abnormal neurological examination (p<0.01) and dysmorphism (p<0.02) in group B. Conclusion.- These results suggested that seizures were more likely for autistic kids who started to walk late and it was less likely to attain verbal ability for them.